FORMATION OF AN INCLUSIVE SOCIETY IN UZBEKISTAN: THE IMPORTANCE OF SOCIO-POLITICAL PROCESSES IN ENSURING THE INCLUSION OF PERSONS WITH DISABILITIES - Makhmanazarova Malika Anvarovna (Frontline Social Sciences and History Journal, 2024)
This article explores the formation of an inclusive society in Uzbekistan, focusing on the socio-political processes that ensure the inclusion of persons with disabilities. It highlights the importance of legal frameworks, awareness-raising initiatives, employment opportunities, community engagement, and mechanisms for monitoring and evaluation. The article argues that a comprehensive approach is essential for promoting the rights of persons with disabilities and creating a more equitable society.